2019
DOI: 10.1152/japplphysiol.00821.2018
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in neural drive and age-related reductions in force steadiness with a cognitive challenge

Abstract: A cognitive challenge when imposed during a low-force isometric contraction will exacerbate sex- and age-related decreases in force steadiness, but the mechanism is not known. We determined the role of oscillations in the common synaptic input to motor units on force steadiness during a muscle contraction with a concurrent cognitive challenge. Forty-nine young adults (19–30 yr; 25 women, 24 men) and 36 old adults (60–85 yr; 19 women, 17 men) performed a cognitive challenge (counting backward by 13) during an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…Muscle damage resulted in increased torque variability during submaximal isometric contractions immediately post exercise, as well as 24 hours after, corroborating previous work (14,49,53,89). This behaviour was observed regardless of age and despite the greater torque variability of older adults at baseline, that has previously been related to the age-related increase in variability of the common synaptic input to motoneurons (12,76). Thus, our results suggest that control of muscle force is equally perturbed in young and older adults following damaging exercise.…”
Section: Disruptions In Motor Performance and Muscle Activitysupporting
confidence: 87%
“…Muscle damage resulted in increased torque variability during submaximal isometric contractions immediately post exercise, as well as 24 hours after, corroborating previous work (14,49,53,89). This behaviour was observed regardless of age and despite the greater torque variability of older adults at baseline, that has previously been related to the age-related increase in variability of the common synaptic input to motoneurons (12,76). Thus, our results suggest that control of muscle force is equally perturbed in young and older adults following damaging exercise.…”
Section: Disruptions In Motor Performance and Muscle Activitysupporting
confidence: 87%
“…We observed a main effect of sex on the variability in MUFR, such that females had greater variability in their MUFR than males in the 20% MVC condition, though this was not observed in the 50% MVC condition. Similarly, at very low contraction intensities and using high-density surface EMG, Pereira et al (2019) demonstrated females have greater oscillations in the common synaptic input than males during single-and dual-task conditions. There is a general paucity of data on sex differences in variability of MUFR at different contraction intensities, thus making the intensity-dependent sex difference observed here a novel observation that should be explored further.…”
Section: Emgmentioning
confidence: 83%
“…These factors, amongst others, are suggested to contribute to a sex difference in force steadiness (Jakobi, Haynes, & Smart, 2018), although the authors concluded that despite a clear sex difference in steadiness, the underlying mechanisms are unclear. One recent investigation using high‐density surface electromyography (Pereira et al., 2019) demonstrated no differences in discharge rate, but showed that females experienced greater oscillations in the common synaptic input to motor units. This greater coefficient of variation in the common synaptic input has been associated with the coefficient of variation of force during sustained submaximal contractions (Farina & Negro, 2015).…”
Section: Sex Differences Within Physiological Systemsmentioning
confidence: 99%